The Neuroprotective Effects of Flavonoid Fisetin against Corticosterone-Induced Cell Death through Modulation of ERK, p38, and PI3K/Akt/FOXO3a-Dependent Pathways in PC12 Cells - Pei-Rong Chang; Je-Wen Liou; Pei-Yi Chen; Wan-Yun Gao; Chia-Ling Wu; Ming-Jiuan Wu; Jui-Hung Yen (MDPI AG, 2023)
The overactive hypothalamic-pituitary-adrenal (HPA) axis is believed to trigger the overproduction of corticosterone, leading to neurotoxicity in the brain. Fisetin is a flavonoid commonly found in fruits and vegetables. It has been suggested to possess various biological activities, including antioxidant, anti-inflammatory, and neuroprotective effects. This study aims to explore the potential neuroprotective properties of fisetin against corticosterone-induced cell death and its underlying molecular mechanism in PC12 cells. Our results indicate that fisetin, at concentrations ranging from 5 to 40 μM, significantly protected PC12 cells against corticosterone-induced cell death. Fisetin effectively reduced the corticosterone-mediated generation of reactive oxygen species (ROS) in PC12 cells. Fisetin treatments also showed potential in inhibiting the corticosterone-induced apoptosis of PC12 cells. Moreover, inhibitors targeting MAPK/ERK kinase 1/2 (MEK1/2), p38 MAPK, and phosphatidylinositol 3-kinase (PI3K) were found to significantly block the increase in cell viability induced by fisetin in corticosterone-treated cells. Consistently, fisetin enhanced the phosphorylation levels of ERK, p38, Akt, and c-AMP response element-binding protein (CREB) in PC12 cells. Additionally, it was found that the diminished levels of p-CREB and p-ERK by corticosterone can be restored by fisetin treatment. Furthermore, the investigation of crosstalk between ERK and CREB revealed that p-CREB activation by fisetin occurred through the ERK-independent pathway. Moreover, we demonstrated that fisetin effectively counteracted the corticosterone-induced nuclear accumulation of FOXO3a, an apoptosis-triggering transcription factor, and concurrently promoted FOXO3a phosphorylation and its subsequent cytoplasmic localization through the PI3K/Akt pathway. In conclusion, our findings indicate that fisetin exerts its neuroprotective effect against corticosterone-induced cell death by modulating ERK, p38, and the PI3K/Akt/FOXO3a-dependent pathways in PC12 cells. Fisetin emerges as a promising phytochemical for neuroprotection.